UPAYA AMERIKA SERIKAT DALAM MEWUJUDKAN PERDAMAIAN DENGAN KELOMPOK TALIBAN DI AFGHANISTAN PERIODE 2017 - 2020 - Nur Intan Savitri, (2022)
This study discusses how the efforts of the United States (US) in realizing peace and describes the peace process with the Taliban group. The emergence of changes in the US strategy in Afghanistan during the Donald Trump administration, namely the intention to make peace with the Taliban group will be studied using Rational Choice Theory (RCT) to see what the advantages and disadvantages have been formulated by the US. Efforts in realizing peace by the US against the Taliban group will be studied using Johan Galtung's concept of Conflict Resolution in three ways, namely peacemaking, peacekeeping, and peacebuilding. The research method used is qualitative with descriptive case study research. Data collection techniques through library research and internet-based research. In this research, the researcher uses data analysis technique according to Miles & Huberman which consists of four stages, namely data collection, data presentation, data reduction, and conclusion/verification. The final result of this study shows that conflict resolution through three ways by the US against the Taliban group can bring about peace between the two. In the peacemaking process, the US held up to ten rounds of peace meetings to reach an agreement with the Taliban group. In the peacekeeping process, the US still maintains its troops in Afghanistan, in case during the peace meeting the Taliban groups continue to carry out acts of violence. The peacebuilding process was marked by the signing of a peace agreement between the US and the Taliban in Doha, Qatar.